American Industry in International Competition Government Policies and Corporate Strategies - Zysman, John; Tyson, Laura (Cornell Studies in Political Economy, 2019)
This book addresses the crucial question of America's adjustment to changes in the international economy. It examines policies that will deal effectively with the continuing erosion of the U.S. share of exports and production in world markets and explores in particular the debate on "industrial policy."